PTU-172 The "sunk" colostomy: a novel corrective approach to achieve satisfactory function. (22nd June 2015) - Siddique, K; Prudhomme, G; Khan, K
Abstract : Introduction: Gastrointestinal stomas are a frequently performed surgical procedure with associated early or late complications. Some of these complications demand advanced technical skills and expertise to manage. We present here a challenging case of sunken colostomy affecting patient's quality of life and a novel approach to achieve a satisfactory functional outcome. Method: Case report : A 63 year old male underwent defunctioning loop colostomy for locally advanced rectal cancer with liver metastasis. Three months later he presented with difficulties managing his stoma. He had developed a horizontal skin crease along the stoma leading to obliteration of stomal opening causing ineffective stoma bag adhesion, resulting in painful parastomal ulcers. The patient was reluctant to consider stoma resiting owing to his job which involved leaning against machinery on his right side. Urgent surgical intervention was required so that his neo-adjuvant therapy would not be delayed. Results: Our novel approach involved the excision of large supero-lateral elliptical fold of anterior abdominal wall down to the fascia with resultant opening up of colostomy. Care was taken to ensure precise excision resulting in flattening of abdominal wall as well as avoidance of future stoma appliance impingement. Conclusion: Discussion : This technique draws parallels to the principles of blepharoplasty of upper eyelids, where droopy eyelid tissue is recontoured to unblock the visual axis. This approach also carried the advantage of operating away from the stoma site thereby preventing potential complication of stomal injury and wound infections. Conclusion: Early successful result has established the feasibility of this novel approach, which has not been reported before. Disclosure of interest: None Declared.